SEISMIC VULNERABILITY OF HIGHWAY BRIDGES IN DKI JAKARTA - MAWAR OKTAVINA, SEKAR
Indonesia is an earthquake-prone country due to its geographical location, which is surrounded by active tectonic plates. Many earthquake occurrences in the past had caused thousands of casualties, thousands of collapsed infrastructures and trillions rupiahs of economic loss. Through these experiences, it is clear that Indonesia must have an adequate prevention and mitigation plan towards earthquake disasters so that the risk can be reduced. The major objective of earthquake disaster risk reduction is to minimalize the fatalities due to earthquake occurrence. However, fatalities are not caused by the earthquake occurrence directly, but are caused by collapsed infrastructures which could harm the surrounding people. Therefore, it is important to assess the vulnerability of infrastructures due to earthquake to prevent fatalities. DKI Jakarta as the capital city of Indonesia holds important socio-economic activities that cover both nationally and internationally. Many infrastructures are built in DKI Jakarta to support those activities despite the fact that DKI Jakarta is also a potential seismic hazard area. Seismic vulnerability assessment of all infrastructures is important to be conducted, however only buildings have been done while highway bridges have not. Therefore, seismic vulnerability of highway bridges in DKI Jakarta is necessary to be assessed to prevent earthquake disaster. The seismic vulnerability is accounted from fragility curve developed by HAZUS under current seismic demand of DKI Jakarta. Though it is addressed for buildings, it will be used as an approach for highway bridges with several adjustments. The fragility curve is a useful tool to describe how vulnerable a bridge to a certain magnitude of earthquake occurrence is in terms of damage state probabilities. The fragility curve is derived from highway bridge models to represent existing bridge in DKI Jakarta and its variations to the structural capacity to address all possible conditions that can affect the probabilities in the fragility curve. There will be six original models to represent existing highway bridges according to its design year. All models have typical configuration which is determined from common existing bridge structural type in DKI Jakarta. The models will be designed according to its respective loading codes, seismic codes, and design codes available in that year. The design focus in this simulation is the earthquake design since it will be different for each design year according to each iii respective seismic code. The performance of the designed models will also be evaluated under current seismic demand using pushover analysis. The study shows that, (1) the newer the codes the more stringent seismic detailing and design that it requires, (2) all models have performance levels in Immediate Occupancy (IO) and Life Safety (LS) range under current seismic demand which indicates that all highway bridges are strong and ductile enough to resist the earthquake forces, (3) the steeper the slope of the fragility curves the more vulnerable the highway bridges to a certain damage state at given Sd value, (4) the more ductile the bridge the less vulnerable it is to a certain damage state, (5) overall, existing highway bridges in DKI Jakarta are not too vulnerable to current seismic demand since the target performance level of life safety or less is more likely to happen.